Remembering Jamestown : hard questions about Christian mission - Yong, Amos.; Zikmund, Barbara Brown (Eugene, Or. : Pickwick Publications, 2010)
This collection of essays deriving from a consultation on missionary history and attitudes in colonial Jamestown, Virginia, explores longstanding assumptions related to Christian mission by listening to Native American voices. What were the ideologies and theologies that motivated early Virginia colonists? How did certain understandings of mission and church provide support and legitimacy for invasion and exploitation? What were, and are, the responses of indigenous populations, and how should Christian mission to Native Americans continue in light of this history? This book addresses these relevant questions and explores ways in which new understandings of Christian mission are needed in the expanding religious and cultural diversity of the twenty-first century--Publisher info.
Introduction: Using Jamestown in 1607 to stimulate questions about Christian mission in 2007 / Barbara Brown Zikmund -- The romance and tragedy of Christian mission among American Indians / Tink Tinker -- A failure to communicate : how Christian missionary assumptions ignore binary patterns of thinking within Native-American communities / Barbara Alice Mann -- Christianity, American Indians, and the doctrine of discovery / Robert J. Miller -- Colonial Virgina mission attitudes toward Native peoples and African-American slaves / Edward L. Bond -- Living in transition, embracing community, and envisioning God's mission as Trinitarian mutuality : reflections from a Native-American follower of Jesus / Richard Twiss -- Salvation history and the mission of God : implications for the mission of the church among Native Americans / Richard E. Waldrop and J. L. Corky Alexander, Jr. -- Jamestown and the future mission : mending creation and claiming full humanity in interreligious partnership / Shanta Premawardhana -- Moving beyond Christian imperialism to mission as reconciliation with all creation / William R. Burrows -- Conclusion: The missiology of Jamestown : 1607-2007 and beyond : toward a postcolonial theology of mission in North America / Amos Yong.
Essays written for and presented at a conference entitled The missiology of Jamestown, 1607, and its implications, held at Regent University, Virginia Beach, Va., May 27-29, 2008.
Includes bibliographical references and indexes.
Keywords: Indians of North America -- Missions -- Virginia -- Jamestown -- History -- 17th century -- Congresses; Missions -- Virginia -- Jamestown -- History -- 17th century -- Congresses; Colonists -- Virginia -- Jamestown -- Attitudes -- History -- 17th century -- Congresses; Jamestown (Va.) -- History -- 17th century -- Congresses; Jamestown (Va.) -- Race relations -- History -- 17th century -- Congresses; Virginia -- History -- Colonial period, ca. 1600-1775 -- Congresses; Indians of North America -- Colonization -- Congresses; Indians of North America -- Missions -- Congresses; Missions -- Moral and ethical aspects -- United States -- Congresses; Postcolonialism -- United States -- Congresses